Odpowiedzi

Najlepsza Odpowiedź!
2010-01-23T15:32:46+01:00
1.(-6-4)²-2²=(-10)²-4=100-4=96
2.(6-10+12)²-(-4+5)³=8²-1³=64-1=63
3.(1 1/2)³-(-1/2)²=(3/2)³-1/4=27/8-2/8=25/8=3 i 1/8=3,125
4.-4²-(-10)⁰=-16-1=-17
5.-[-(-5)²+(-1)³]=-[-25+(-1)]=-[-26]=26
6.-125 ⁰-(-5)³=-1-(-125)=-1+125=124
2010-01-23T16:52:19+01:00
1.(-6-4)do potęgi2-2do potęgi2= (-10) do potęgi2 -4=100-4=96
2.(6-10+12)do potęgi2-(-4+5)do potęgi3=8 do potęgi 2-1do potęgi 3=64-1=63
3.(1 1/2)do potęgi3-(-1/2)do potęgi2= 9=(3/2) do potęgi 3 -1/4=27/8 - 2/8=
=25/8= 3 i 1/8
4.-4do potęgi2-(-10)do potęgi0= -16-1=-17
5.-[-(-5)do potegi2+(-1)do potęgi3]= -[-25-1]= -[-26]=26
6.-125 do potęgi0-(-5)do potęgi3=-1-(-125)=-1+125=124